Animal Acts : Performing Species Today. - Chaudhuri, Una.; Hughes, Holly (Ann Arbor : University of Michigan Press, 2014)
Encounters between the species in an anthology of lively solo performances and commentary.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books